1996
DOI: 10.1046/j.1526-4610.1996.3604243.x
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Pollution and Headache

Abstract: The aim of this study was to clarify a possible relationship between pollution and worsening of headache in the industrial city of Turin. From October 1992 to June 1993, we examined a group of 32 patients suffering from various headache types. During these months, they kept a daily record of their headaches and associated disturbances. Changes in pain frequency and severity were recorded every hour of the day and compared hour to hour with the various degrees of pollution recorded in the main streets by a moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…We detected significant effects of carbon monoxide, nitrogen dioxide, and particulates on ED visits for headache. This result agrees with those reported in the literature [7]. In addition, we verified the results by performing the analysis separately for some cities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We detected significant effects of carbon monoxide, nitrogen dioxide, and particulates on ED visits for headache. This result agrees with those reported in the literature [7]. In addition, we verified the results by performing the analysis separately for some cities.…”
Section: Discussionsupporting
confidence: 92%
“…Air quality in the home [3], office environment [4,5], and the occupational setting [6] may also exacerbate headaches. A daily diary study of 32 headache sufferers in Italy revealed that the severity and frequency of headaches was related to days with higher concentrations of carbon-monoxide and nitrogen dioxide [7]. Headaches were more commonly reported from a neighbourhood with a pulp mill, with higher sulphur dioxide (SO 2 ) emissions, compared to one without [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are only two references on outdoor air pollution and they report a positive association with headache (Marttila et al, 1994;Nattero and Enrico, 1996). Moreover, a study by Wilkinson et al (1994) shows that by the way of bronchial responsiveness, asthma may be an independent risk factor for frequent headache in children, after adjusting for age and smoking in the home (RR ‫ס‬ 3.24, 95% CI ‫ס‬ 2.19-4.77).…”
Section: Figmentioning
confidence: 99%
“…Air quality in the home [3], office environment [4,5], and occupational setting may play a role in the exacerbations of migraine headache [6]. A daily diary study of 32 headache sufferers in Italy revealed that the severity and frequency of headaches correlated with days when elevated concentrations of carbon monoxide and nitrogen dioxide were recorded [7]. In another study, the headache reported was more common in a neighborhood with a pulp mill, compared to one without [8].…”
Section: Introductionmentioning
confidence: 99%